THE EFFECT OF COMPANY ACTIVITIES ON DEBT COMPOSITION AND PROFITABILITY ON PUBLIC COMPANIES IN INDONESIAN FOOD AND BEVERAGE INDUSTRY - Robin Jonathan, LCA; Militina, Theresia (Archives of Business Research, 2020)
This study aims to analyze the effect of company activities which projected in the Total Asset Turn Over (TATO), Inventory Turn Over (ITO), and Fixed Asset Turn Over (FATO) variables on Debt Composition (DAR) and Net Profit Margin (NPM) on Indonesian Public companies in food and beverages sector during 2013-2019. The research data is sourced from 21 issuers, 7 issuers do not include financial statements and losses, therefore the sample size is 14 issuers. Data were analyzed using multiple linear regression analysis and path analysis. The results showed that simultaneous company activities: TATO, ITO and FATO have significant effect on DAR and NPM. DAR has no significant effect in mediating the influence of TATO, ITO and FATO on NPM. Overall, DAR played a role in weakening TATO’s influence on NPM. As for ITO and FATO, DAR played a role in strengthening ITO’s influence and FATO’s influence on NPM.